Discovery of New Therapeutic Targets by the Informational Spectrum Method - Veljkovic, Nevena; Glisic, Sanja; Prljic, Jelena; Perovic, Vladimir; Botta, Maurizio; Veljkovic, Veljko (Current Protein and Peptide Science, 2008)
The field of bioinformatics has become a major part of the drug discovery pipeline playing a key role in improvement and acceleration of this time and money consuming process. Here we review the application of the informational spectrum method (ISM), a virtual spectroscopy method for structure/function analysis of proteins, in identification of functional protein domains representing candidate therapeutic targets for drugs against human immunodeficiency virus (HIV)-1, anthrax, highly pathogenic influenza virus H5N1 and cardiovascular diseases.
Keywords: H5N1